Seed Germination Enhancement of Ziziphus spina-christi (L.) Willd. and Ziziphus mucronata Willd. (Rhamnaceae) Using Different Pre-sowing Treatments in Ethiopia - Seid, Mohammed Adefa; Wondimu, Tigist; Degu, Asfaw; Assefa, Awol (Annals of Arid Zone, 2024)
The stony endocarp and impermeable seed coat of Ziziphus, including fleshy mesocarp inhibit seed germination in both genera. In present study effects of different pre-sowing treatments on seed germination of Z. spina-christi and Z. mucronata was studied. Seeds of each species were collected from the Central and Southern Rift Valley and Northeast Ethiopia. Seeds of each Ziziphus species, after being divided into cracked and uncracked seed-stone groups were subjected to eight different pre-sowing treatments and planted in pots. The mean germination percentage (GP), mean daily germination (GD), mean germination time (GT), and mean germination index (GI), as well as two-way ANOVA and Tukey’s Honestly Significant Difference (THSD), were computed. The two-way ANOVA showed that there exists a significant mean difference among treatment groups under all germination parameters at p<0.05 for both species. The THSD for Z. spina-christi showed that the highest GP was achieved by cracked seed stones soaked in cold water for 48 hours at a room temperature of 25°C (52.7±6), control (48.5±3), soaked in cold water for 24 hours at a room temperature of 25°C (46.5±5.7), and rubbed with sandpaper (41±12.1), which are significantly different at p<0.05, while the highest GI was recorded by cracked seed stones soaked in cold water for 48 hours at a room temperature of 25°C (1.3±0.2), which is significantly different at p<0.05. The THSD for Z. mucronata indicated that the highest GP, along with the highest GI, was achieved by cracked seed stones soaked in 98% H2SO4 for 20 minutes and subsequently rinsed with water (28.5±6), which is significantly different at p<0.05. Overall, the findings of this study will contribute to potential seed enhancement technologies for Ziziphus, with greater implications for the propagation, conservation, and sustainable utilization of the species in the agricultural and pastoral communities of Ethiopia.